2009
DOI: 10.1016/j.etp.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of liver toxicity in F344/N rats and B6C3F1 mice after exposure to a flame retardant containing lower molecular weight polybrominated diphenyl ethers

Abstract: Lower molecular weight polybrominated diphenylethers (PBDEs), components of flame retardants, are found in the environment and in human and animal tissues. Toxicity studies were conducted in F344/N rats and B6C3F1 mice by administering a flame retardant containing these lower molecular weight PBDEs (BDE-47, BDE-99, BDE-100, and BDE153) by oral gavage 5 days/week for 13 weeks at doses of 0.01, 5, 50, 100 or 500 mg/kg/day. Liver was the primary target organ in rats and mice. Treatment-related increases in liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 37 publications
2
20
1
Order By: Relevance
“…This differs from the results of other recent studies where hepatic cell damages were found (Raldúa et al, 2008;Dunnick and Nyska, 2009). Factors such as different animal species and doses could explain these differences.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This differs from the results of other recent studies where hepatic cell damages were found (Raldúa et al, 2008;Dunnick and Nyska, 2009). Factors such as different animal species and doses could explain these differences.…”
Section: Discussioncontrasting
confidence: 85%
“…It has been reported that oral exposure to lower brominated congeners induces hepatic hypertrophy and increases liver weight (IPCS, 1994;Dunnick and Nyska, 2009). Moreover, a number of studies have shown that exposure to PBDEs seems to induce an increase in hepatic microsomal enzyme activities involved in the metabolism of xenobiotics (Zhou et al, 2001;Wolkers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This liver toxicity in the Wistar Han rat is similar to that observed in the F344/N rat after PBDE exposures (Dunnick and Nyska 2009). Hepatocellular vacuolization, as seen in PBDE rat livers, is often indicative of accumulation of fat deposits (Eustis et al .…”
Section: Discussionsupporting
confidence: 80%
“…PBDE-induced liver toxicity and alterations in liver enzyme levels, and, thus, metabolic activation is a likely mechanism for this toxicity. Dunnick and Nyska (2009) demonstrated that increases in liver weights and induction of liver cytochrome P450 (1A1, 1A2, 2B) and UDPGT levels were observed in both rats and mice after BDE-exposure. In addition, hepatocyte hypertrophy and vacuolization increased in incidence and severity with treatment, and occurred at levels of 50 mg/ kg and above in rats.…”
Section: Discussionmentioning
confidence: 99%